Quality of relationships as predictors of outcomes in people with dementia: a systematic review protocol. Issue 4 (4th April 2016) - Edwards, Hannah B; Savović, Jelena; Whiting, Penny; Leach, Verity; Richards, Alison; Cullum, Sarah; Cheston, Richard
Abstract : Introduction: Serious adverse outcomes for people with dementia include institutionalisation, hospitalisation, death, development of behavioural and psychiatric symptoms, and reduced quality of life. The quality of the relationship between the person with dementia and their informal/family carer is thought to affect the risk of these outcomes. However, little is known about which aspects of relationship quality are important, or how they affect outcomes for people with dementia. Methods and analysis: This will be a systematic review of the literature. Electronic databases MEDLINE, EMBASE, Web of Science, PsycInfo, the Cochrane Database, ALOIS and OpenGrey will be searched from inception. 2 independent reviewers will screen results for eligibility with standardised criteria. Data will be extracted for relevant studies, and information on the associations between relationship quality and dementia outcomes will be synthesised. Meta-analysis will be performed if possible to calculate pooled effect sizes. Narrative synthesis will be performed if study heterogeneity rules out meta-analysis. Ethics and dissemination: Ethical review is not necessary as this review summarises data from previous studies. Results will be disseminated via peer-reviewed publication. Results will also be disseminated to a patient and public involvement group and an expert panel for their views on the findings and implications for future work. Trial registration number: CRD42015020518.